Combinatorial therapy for triple negative breast cancer using hyperstar polymer-based nanoparticles. Issue 93 (5th October 2015) - Misra, S. K.; Wang, X.; Srivastava, I.; Imgruet, M. K.; Graff, R. W.; Ohoka, A.; Kampert, T. L.; Gao, H.; Pan, D.
Abstract : We report the ability of a novel combinatorial therapy obtained from nanoparticles of hyperstar polymers encompassing drugs to selectively target triple negative breast cancer (TNBC) cell proliferation through STAT3 and topoisomerase-II pathways. Abstract : We report the ability of a novel combinatorial therapy obtained from nanoparticles of hyperstar polymers encompassing drugs to selectively target triple negative breast cancer (TNBC) cell proliferation through STAT3 and topoisomerase-II pathways. This nano-cocktail was at least two to four fold better than the individual drugs and 6–20 times more selective than the parent drugs.